Replays, rivalries, and rumbles : the most iconic moments in American sports - Gietschier, Steven Philip, 1948- (University of Illinois Press, 2017)
"What were the iconic sports moments of the last century? In Replays, Rivalries, and Rumbles, a team of sports aficionados climb onto their bar stools to address that never-solved but essential question. Triumphs and turning points, rivalries and record-setters "each chapter tracks down the real story behind the epic moments and legendary careers sports fans love to debate. Topics include Abner Doubleday and the origins of baseball; the era-defining 1979 duel between Larry Bird and Magic Johnson; how Denver and Cleveland relive The Drive; the myths surrounding the Ali-Foreman Rumble in the Jungle; Billie Jean King's schooling of Bobby Riggs; the Miracle on Ice; and ESPN's conquest of the sports world. Filled with eye-opening lore and analysis, Replays, Rivalries, and Rumbles is an entertaining look at what we think we know about sports"--